Demand of pharmaceutical facility functionality: Validation and qualification of HVAC system - Singh, Anamika; Malviya, Sapna; Kharia, Anil (Asian Journal of Pharmaceutics (AJP), 2014)
Heating, ventilation, and air system encompasses heating, ventilation, and air conditioning, which is integral component of pharmaceutical facility functionality. The system is needed for maintenance of a suitable temperature, for continuous flow of air, which ultimately prevents cross‑contamination and accumulation of air and to ensure the cooling of air in the premises. The three core facets of HVAC system validation comprises of installation qualification (IQ), operational qualification (OQ), and performance qualification (PQ). Validation of HVAC system is an essential subject to provide documented evidence about the accuracy of results produced by it. The validation of HVAC system involves systemized and assembled documents of functional specifications; design drawings, plans, and specifications; validation master plan; testing, adjusting, and balancing (TAB); and startup reports. The various parameters to be evaluated for the validation of HVAC system include air flow pattern, air flow velocity, air changes per hour, filter leak test, particle count, viable monitoring, filter integrity test, pressure difference, recovery test for temperature and humidity, temperature and humidity uniformity, and fresh air determination. Key words: Heating, qualification, validation, ventilation and air conditioning